KONTEKTUALISASI HADIS LARANGAN MENGGAMBAR DENGAN PEMBELAJARAN MENGGAMBAR PADA PENDIDIKAN ANAK USIA DINI - Isliyanto (Jurnal Payung Sekaki : Kajian Keislaman, 2024)
Early childhood education is generally unavoidable from the activities of drawing in the learning process. There is a history of the Hadith that prohibits a person from drawing, and the prohibition is accompanied by a severe punishment. Of course this is a special thought for artists of painting or painting and those engaged in the activities of drawing, including early childhood educators. So this article is meant to trace the understanding of the hadith about the prohibition of drawing and try to contextualize that understanding with early childhood education. This research combines the research of the library that is analyzed with the content alaysist approach through the understanding of fiqh al-hadis.